The concept of acclimatization - Monge M., Carlos (1956)
According Coon and Birsdell Coon one of the main factors in the differentiation of modern breeds have been natural selection operating on terms and incentives inherent in extreme environments. In the fourth glacial period the mongólioa race was the last to differentiate developed huge breasts, short limbs and globular bodies radiate little heat as possible. Mongolia is a plateau with an average altitude of 1,500 meters. Summers are hot and winters cold. Their migrations reach the 60 degree north latitude. The climatic environment corresponds to extreme cold, extreme altitude, and extreme anoxia as in the highlands of the Himalayas and the Andes whose inhabitants have the same characteristics.